Hemoplasmas in wild canids and felids in Brazil - André, Marcos Rogerio [UNESP]; Adania, Cristina Harumi; Allegretti, Silmara Marques; Machado, Rosangela Zacarias (BioOne, 2011)
Hemotropic mycoplasmas, epicellular erythrocytic bacterial parasites lacking a cell wall, are the causative agents of infectious anemia in numerous mammalian species. The presence of hemotropic mycoplasmas in blood samples of neotropical and exotic wild canids and felids from Brazilian zoos were recorded using molecular techniques. Blood samples were collected from 146 Brazilian wild felids, 19 exotic felids, 3 European wolves (Canis lupus), and from 97 Brazilian wild canids from zoos in the Brazilian states of São Paulo and Mato Grosso and the Federal District. Using conventional polymerase chain reaction (PCR), this work found 22 (13%) wild felids positive to Candidatus Mycoplasma haemominutum [4 jaguars (Panthera onca); 3 pumas (Puma concolor); 10 ocelots (Leopardus pardalis); 2 jaguarondis (Puma yagouaroundi); and 3 little spotted cats (Leopardus tigrinus)]. Only one little spotted cat (Leopardus tigrinus) was positive to Mycoplasma haemofelis, and none was positive to Candidatus Mycoplasma turicensis. Two bush dogs (Speothos venaticus) were positive for a Mycoplasma sp. closely related to Candidatus Mycoplasma haematoparvum, and two European wolves were positive for a Mycoplasma sp. closely related to Candidatus Mycoplasma haemominutum. This is the first study regarding the molecular detection of hemotropic mycoplasmas in wild canids.